A new insight to explore the regulation between S‐nitrosylation and N‐glycosylation. (1st March 2019) - Du, Hu; Chen, Lichao; Zhan, Ni; Mu, Jinye; Ren, Bo; Zuo, Jianru
Abstract: Nitric oxide (NO) is a signal molecule in plants and animals. Arabidopsis GSNO reductase1 (AtGSNOR1) catalyzes metabolism of S ‐nitrosoglutathione (GSNO) which is a major biologically active NO species. The GSNOR1 loss‐of‐function mutant gsnor1‐3 overaccumulates GSNO with inherent high S ‐nitrosylation level and resistance to the oxidative stress inducer paraquat (1, 1′‐dimethyl‐4, 4′‐bipyridinium dichloride). Here, we report the characterization of dgl1‐3 as a genetic suppressor of gsnor1‐3 . DGL1 encodes a subunit of the oligosaccharyltransferse (OST) complex which catalyzes the formation of N ‐glycosidic bonds in N ‐glycosylation. The fact that dgl1‐3 repressed the paraquat resistance of gsnor1‐3 meanwhile gsnor1‐3 rescued the embryo‐lethal and post‐embryonic development defect of dgl1‐3 reminded us the possibility that S ‐nitrosylation and N ‐glycosylation crosstalk with each other through co‐substrates. By enriching glycoproteins in gsnor1‐3 and mass spectrometry analysis, TGG2 (thioglucoside glucohydrolase2) was identified as one of co‐substrates with high degradation rate and elevated N ‐glycosylation level in gsnor1‐3 ost3/6 . The S ‐nitrosylation and N ‐glycosylation profiles were also modified in dgl1‐3 and gsnor1‐3 . Thereby, we propose a linkage between S ‐nitrosylation and N ‐glycosylation through co‐substrates.